Ð Ð¾Ð»ÑŒ Ñ„Ð°ÐºÑ‚Ð¾Ñ€Ð° Ñ€Ð¾ÑÑ‚Ñƒ Flt-3 Ñƒ Ñ€ÐµÐ³ÑƒÐ»ÑÑ†Ñ–Ñ— Ð¿Ñ€Ð¾Ð»Ñ–Ñ„ÐµÑ€Ð°Ñ‚Ð¸Ð²Ð½Ð¾Ñ— Ð°ÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚Ñ– ÐÐ¡133+ ÐºÐ»Ñ–Ñ‚Ð¸Ð½ ÐºÐ¾Ñ€Ð´Ð¾Ð²Ð¾Ñ— ÐºÑ€Ð¾Ð²Ñ– - Bilko, N. M.; Vasilovskaya, S. V.; Bilko, D. I.; Votyakova, I. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
AC133+ fraction of the cord blood cells separated by magnetic bead sorting was incubated with (10 ng/ml) during 12–18 hours that induced statistically significant enrichment of the colony formation in vitro of functionally active hematopoietic progenitor cells.